The Synthetic Retinoid Acitretin Increases IL-6 in the Central Nervous System of Alzheimer Disease Model Mice and Human Patients - dos Santos Guilherme, Malena; Stoye, Nicolai M.; Rose-John, Stefan; Garbers, Christoph; Fellgiebel, Andreas; Endres, Kristina (Frontiers in Aging Neuroscience, 2019)
These days the important role of retinoids in adult brain functionality and homeostasis is well accepted and has been proven by genomic as well as non-genomic mechanisms. In the healthy brain, numerous biological processes e.g. cell proliferation, neurogenesis, dendritic spine formation as well as modulation of the immune system have been attributed to retinoid signaling. This, together with the finding that retinoid metabolism is impaired in Alzheimer’s disease, led to preclinical and early clinical testing of natural and synthetic retinoids as innovative pharmaceuticals with multifactorial properties. Acitretin, an aromatic retinoid, was found to exert anti-amyloidogenic effect in mouse models for Alzheimer’s disease as well as in human patients by stimulating the alpha-secretase ADAM10. The lipophilic drug was already demonstrated to easily pass the blood brain barrier after i.p. administration and increased nest building capability in the 5xFAD mouse model. Additionally, we analyzed the immune-modulatory capacity of acitretin via a multiplex array in the 5xFAD mouse model and evaluated some of our findings in human CSF derived from a pilot study using acitretin. Although several serum analytes did not display changes, IL-6 was found to be significantly increased in both - mouse and human neural material. This demonstrates that acitretin exerts an immune stimulatory effect – besides the alpha-secretase induction – which could impact the alleviation of learning and memory disabilities observed in the mouse model.